Rural Teachers’ Cultural and Epistemic Shifts in STEM Teaching and Learning - Tofel-Grehl, Colby; Searle, Kristin A.; Hawkman, Andrea; MacDonald, Beth L.; Suárez, Mario I. (Theory & Practice in Rural Education, 2021)
This article focuses on the ways in which integrated curriculum can improve STEM teaching and learning within rural spaces. Using a design-based research approach, this study focuses on rural teachers' experiences of professional learning and development training as they learn to engage computing and maker technologies in their elementary classrooms as tools for teaching students about difficult histories of immigration, migration, and forced relocation across the United States.